Study the Role of Congenital Toxoplasmosis with Preterm Labor, and Low Birth Weight - Al-Bayati, Asmaa M S (Journal for Research in Applied Sciences and Biotechnology, 2023)
The study included 100 samples of blood from women who suffer from premature birth and low fetal weight, and a hundred samples from women who do not suffer from any injury. This study extends from February 1, 2019 to November 1, 2019, where the study included collecting blood samples from all women who entered the study, in addition to collecting information regarding age, weight, height, and history of infection with parasites, if any, to investigate the parasite’s DNA in blood samples collected from patients. These samples were examined using the standard methods provided by the company in which the tests were conducted. The study included the molecular detection by PCR of toxoplasma genes, where EDTA blood samples were collected from all preterm and term pregnant women in the study. Using laboratory kit for Toxoplasma DNA extraction, samples were extracted and kept in separate sterile tubes using DAN extraction kit (Zymogene, Japan), then the DNA was detected by real-time PCR which was done according to the protocols designed by the manufacturer of the diagnostic kit. The study showed no significant relationship between the two groups regarding mean of ages. But regular contractions, reduced length of cervix and decreased weight of babies was highly related with women presented with preterm birth. The study showed that 87.5% of preterm delivery women with +ve DNA detection of T. gondii have regular contraction comparing with 12.5% of cases with negative T. gondii infection (P<0.001). The study showed the lowest mean of baby weight at birth was recorded in pregnant women with preterm labor women who infected with T. gondii as compared with cases who were negative to T. gondii infection (P<0.001). The study demonstrated that majority of women with +ve T gondii infection were had positive history of abortion.